Robotic gastrectomy for gastric cancer—an American perspective - Goldner, Bryan; Woo, Yanghee (Translational Gastrointestinal Cancer, 2015)
Gastric cancer is a challenging surgical disease in the United States. Most patients present with advanced disease, curative resection requiring radical gastrectomy with D2 lymphadenectomy within a multimodality treatment approach. Minimizing surgical trauma is imperative to the goals of long-term survival and a good quality of life for our gastric cancer patients. The patient’s early recovery from surgery with the ability to return to normal daily activities and to receive timely adjuvant treatment is an essential part of the comprehensive treatment for locally advanced gastric cancer. Therefore, limiting the surgical insult while maximizing the oncologic efficacy is a major consideration when deciding on the surgical approach. Robotic radical gastrectomy with its favorable outcomes is a promising option for expanding the currently limited role of minimally invasive surgery for gastric cancer in the United States. The minimally invasive approach to gastric cancer surgery offers patients improved clinical outcomes without compromising the oncologic efficacy of the operations in comparison to the open approach. These proven benefits for early gastric cancers have led to several large-scale prospective investigations of laparoscopic surgery for advanced gastric cancer in East Asia. While awaiting their conclusive results, many experienced gastric cancer surgeons have already extended their indications for minimally invasive surgery to include advanced gastric cancer. Conceptually, no detrimental differences in long-term survival outcomes are expected for minimally invasive radical gastrectomy when properly performed. To do so require achieving negative margins, evaluating sufficient number of lymph nodes, and dissecting the appropriate level of lymph node stations. Unfortunately, the technical difficulty and the challenges of D2 lymphadenectomy in advanced gastric cancer patients will continue to impede the adoption of laparoscopic surgery for relatively lower volume surgeons in the United States. Robotic radical gastrectomy using the Da Vinci Si/Xi Surgical Systems (Intuitive Surgical, Sunnyvale, CA, USA) promises to facilitate the adoption of minimally invasive surgery for gastric cancer worldwide. In the United States, the surgeon’s ability to control four robotic instruments and capitalize on the 3-dimension (3D) magnified operative view, the Endowristed capability with 7-degree of articulation, and the tremor filtering of the instrument movements, may prove especially useful to overcoming the steep learning curve of this complex oncologic operation. The critical translation of these and other new robotic surgical tools into appropriate clinical practice for the ultimate benefit of our gastric cancer patients will determine the future of robotic surgery; not only in gastric cancer, but for all complex abdominal operations.